(Trans)forming the political (cis)tem? Notes on the 2020 municipal elections from the perspective of gender and sexuality studies (Research, Society and Development, 2022)
In this article we intend to outline the necessary debates on the participation of the LGBTQIA+ community in brazilian politics in the last municipal elections (2020). Above all, we want to reflect on the candidacies, and for this purpose, the election of people who identify as trans women or men, transvestites, transsexuals or other trans identities. Methodologically, the study is characterized by being qualitative-descriptive, based on an analysis of bibliographic and documentary review of journalistic reports about the trans people elections published on different websites and two materials prepared and published on the ANTRA's website– National Association of Transvestites and Transsexuals of Brazil. In total, 04 reports from national newspapers and 02 reports published on the ANTRA website about the requests of these social actors in the national territory were analyzed. As a result, in general terms, we can highlight that the work allowed to raise a discussion on the importance of the candidacies of trans people in the field of national politics, therefore providing opportunities for public policies, discussions and deliberations in favor of this social segment, historically marginalized.